2014
DOI: 10.3390/molecules19021843
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Activity and Induction of Apoptosis in PC-3 Cells by the Chalcone Cardamonin from Campomanesia adamantium (Myrtaceae) in a Bioactivity-Guided Study

Abstract: Abstract:The Myrtaceae family is a common source of medicines used in the treatment of numerous diseases in South America. In Brazil, fruits of the Campomanesia species are widely used to make liqueurs, juices and sweets, whereas leaves are traditionally employed OPEN ACCESSMolecules 2014, 19 1844 as a medicine for dysentery, stomach problems, diarrhea, cystitis and urethritis. Ethanol extracts of Campomanesia adamantium (Myrtaceae) leaves and fruits were evaluated against prostate cancer cells (PC-3). The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 28 publications
(33 reference statements)
5
45
0
1
Order By: Relevance
“…It is a native shrub with yellow flowers found in Uruguay and Southern Brazil (Ferraz et al 2009 ). Phenolic compounds, including flavonoids, chromones, chalcones and phenolic acids, have displayed a broad range of biological properties such as antiproliferative (Pascoal et al 2014), anti-inflammatory (Min & Cuong 2013), antioxidant (Charles & Venkata 2014), trypanocidal (Marin et al 2011) and leishmanicidal (Ogungbe et al 2014). In the course of our investigation, nine phenolic derivatives were isolated and identified from C. uniflora.…”
Section: Introductionmentioning
confidence: 98%
“…It is a native shrub with yellow flowers found in Uruguay and Southern Brazil (Ferraz et al 2009 ). Phenolic compounds, including flavonoids, chromones, chalcones and phenolic acids, have displayed a broad range of biological properties such as antiproliferative (Pascoal et al 2014), anti-inflammatory (Min & Cuong 2013), antioxidant (Charles & Venkata 2014), trypanocidal (Marin et al 2011) and leishmanicidal (Ogungbe et al 2014). In the course of our investigation, nine phenolic derivatives were isolated and identified from C. uniflora.…”
Section: Introductionmentioning
confidence: 98%
“…The exposition periods for cell viability and antiproliferative assays were 24 and 48 h, respectively. Doxorubicin hydrochloride was used as positive control at concentrations of 0.043 to 430 μ m , equivalent to 0.025 to 250 μg/ml . Negative control included untreated cells grown in the supplemented DMEM/F12.…”
Section: Methodsmentioning
confidence: 99%
“…The main components of C. adamantium extract are chalcones, flavonones, and phenolic compounds (Ramos et al, 2007;Coutinho et al, 2008;Ferreira et al, 2013;Pascoal et al, 2011Pascoal et al, , 2014. Compounds belonging to the chemical classes such as flavonones and chalcones are known to affect the metabolizing activity of microsomal fraction of liver (Shimada et al, 2010;Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…This speculation is supported by the effect observed at lower doses; the initial damage caused by the extract is less extensive and can still be detected as increased number of micronuclei over 24 h. After 48 and 72 h, micronucleus frequency decreased, and damage may be detected as increased number of apoptotic cells. Pascoal et al (2014) reported the cytotoxic potential of ethanolic extract from leaves and fruit of C. adamantium, and a chalcone isolated from leaves, referred to as cardamonin. In a prostate cancer cell line (PC-3), leaf extract demonstrated optimal antiproliferative response, which was associated with higher level of cardamonin.…”
Section: Discussionmentioning
confidence: 99%